Strategic Management of the Department of Education and Culture in Improving the Quality of Education in Banda Aceh City - Nimmi Fauziah Pohan; Murniati Murniati; Bahrun Bahrun (AL-ISHLAH: Jurnal Pendidikan, 2023)
The function of management is crucial in enhancing the quality of education. The objective of this research is to ascertain: (1) a strategic initiative for enhancing the standard of education; (2) the strategic execution of measures aimed at improving the quality of education; (3) the strategic assessment of efforts made to enhance the quality of education; and (4) the factors that exert influence on the improvement of educational quality. The study employs qualitative methodologies. The data collection methods employed in this study encompassed interviews, observations, and documentation analysis. The research participants included the head of the Banda Aceh city education and culture office, the principal, and the school supervisor. The methodology employed for data analysis is descriptive qualitative analysis, accompanied by a series of data processing procedures, including data reduction, data display, and the formulation of conclusions, followed by data verification. The results showed that: (1) the strategic program in improving the quality of education was adjusted to the vision and mission of the city of Banda Aceh and carried out a SWOT analysis first as a policy in the future; (2) The implementation of the strategic program begins with the placement of certain structural and functional officials according to Anjab from functional teachers, former principals and school supervisors, maximizing the role of all stakeholders to be responsible for the tasks and functions that have been carried out, carrying out the guidance of school principals, teacher training, and education staff development; (3) Strategic evaluation in improving the quality of education is carried out through regular meetings with school principals, school supervisors every Tuesday, evaluation is carried out by asking for accountability reports for each activity; and (4) supporting factors, namely the strategic location of the education and culture office which is in the center of the capital city of Aceh province, the close distance from each school to the Banda Aceh City Education and Culture Office. The findings indicated that the presence of supplementary media resources and the willingness of educators and school administrators to participate in professional development activities were significant factors.